FIRST FINDS OF AN ICHTHYOFAUNA IN MIDDLE CARBONIFEROUS STRATA OF THE TUNGUSKA SYNECLISE - Yesin D.N.; Ustinov V.N.; Shatalov V.I.; Saltykov O.G. (My University, 1990)
The study of the upper Paleozoic strata on the eastern flank of the Tunguska syneclise and establishment of their paleogeographic context is connected with the search for valuable kimberlite minerals in placer and bedrock deposits of middle Paleozoic age. The discovery of a brackish-water or marine ichtyofauna in these deposite is of great interest with respect to paleogeographic reconstructions. Our fish finds in the Middle Carboniferous deposits of the eastern flank of the Tunguska syneclise clarify the paleogeography of this region at the beginning of the late Paleozoic. Thus, 1. During the first half of the Middle Carboniferous (Yangotoyian) there existed both continental and marine depocenters. 2. The Middle Carboniferous siltstone containing fish remains was deposited in estuaries, lagoons and other marginal parts of a freshened marine basin. 3. Incursion of marine waters from the inner parts of the Tunguska syneclise during the first half of the Middle Carboniferous was relatively short-lived and was associated with transgressive stages in the development of seas of northern and southern Siberia.
Keywords: Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная